Analisis Madzhab Syafi’i Terhadap Fatwa MUI tentang Akad Qardh - Abdul Kholiq Syafa’at; M. Afnan Afandi (IAI Darussalam, 2020)
The purpose of this research is to analyze the Syafi'i Madzhab against the MUI fatwa regarding the Qardh Akad. The type of research used is qualitative research and is descriptive analysis. The MUI fatwa which explains al-Qardh itself has been stated in the MUI DSN fatwa No. 19 / DSN-MUI / IV / 2001 on al-Qardh which includes; general provisions, sanctions, sources of funds, and other provisions. The research method is a qualitative method with a naturalistic type. The results of this study conclude that the DSN-MUI Fatwa regarding the Qardh contract is following the qardh concept established by the Syafi'i school, both in terms of law and its consequences, it's just that there are several points from the fatwa researchers have not been able to conclude through the mu'tabarah books of the Shafi'i school